2005
DOI: 10.1111/j.1582-4934.2005.tb00509.x
|View full text |Cite
|
Sign up to set email alerts
|

Cajal-type cells from human mammary gland stroma: phenotype characteristics in cell culture

Abstract: We report here the in vitro isolation of Cajal-like interstitial cells from human inactive mammary-gland stroma. Primary cell cultures examined in phase-contrast microscopy or after vital methylene-blue staining revealed a cell population with characteristic morphological phenotype: fusiform, triangular or polygonal cell body and the corresponding (very) long, slender, moniliform cytoplasmic processes. Giemsa staining pointed out the typical knobbed aspect of cell prolongations. Immunofluorescence (IF) showed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 19 publications
(22 reference statements)
1
28
0
Order By: Relevance
“…Also, we described the phenotype characteristics of mammary ICLC in primary cell cultures [19]. However, the unequivocal identification of ICLC outside the gut requires, for the time being, the obligatory use of TEM [5].…”
Section: Introductionmentioning
confidence: 99%
“…Also, we described the phenotype characteristics of mammary ICLC in primary cell cultures [19]. However, the unequivocal identification of ICLC outside the gut requires, for the time being, the obligatory use of TEM [5].…”
Section: Introductionmentioning
confidence: 99%
“…Using methylene blue dye or heavy metal impregnation techniques, he demonstrated that interstitial cells stained differently from nerve cells with which they kept a close spatial relationship. Nowadays, these interstitial cells were found in a wide variety of organs [3] including pancreas [4], urinary tract [5][6][7], uterus [8,9], fallopian tube [10], mammary gland [11,12], heart [13][14][15], blood vessel wall [16,17] and, indeed, gastrointestinal tract [18].…”
mentioning
confidence: 99%
“…Giemsa stains previously identified ICLCs in the mammary gland stroma (Radu et al, 2005) and the fallopian tube (Popescu et al, 2005a). According to our findings, this stain is also reliable in identifying the PICCs/ portal telocytes, before any immunohistochemical labeling.…”
Section: Discussionmentioning
confidence: 68%